Deformation behaviour of concrete materials under the sulfate attack. (20th June 2019) - Sun, Dandan; Wu, Kai; Shi, Huisheng; Miramini, Saeed; Zhang, Lihai
Highlights: A coupled chemo-mechanical model was developed using poro-elastic theory. The Hill Function was used to describe the relationship between ettringite generated stress and ettringite concentration. The model can reproduce the experimental observed time-dependent elastic deformation behaviour of concrete. The effect of ettringite and gypsum on the effective diffusion coefficient of sulfate ions was researched. Abstract: This study developed an integrated computational model to predict the time-dependent elastic deformation behaviour of concrete materials under external sulfate attack. The reactive-transport process of ions, pore size dependent diffusion coefficient and internal stress development induced by the ettringite formation inside the concrete pores are all considered in the model. Experiments of longitudinal expansion of specimens under different concentration of sulfate ions are carried out to validate the model predictions. Results show that the model can reproduce the experimental observed elastic deformation behaviour of concrete by using one set of model parameters and the relationship between ettringite generated pressure and ettringite concentration could be described by Hill Function. It indicates that the internal stress induced by ettringite formation initially increases at a relatively slow rate until its concentration reaches 20% of the maximum allowable concentration cEtt_max, at which a significant increase of internal expansive stress is triggered, and finally the change of the internal stress gradually keep a stable state when ettringite concentration is over 50% of cEtt_max . Furthermore, it demonstrates that under the influence of accumulation of reaction product, the diffusion coefficient of sulfate ion decreases with time and a relatively high sulfate concentration reduces the time required for concrete to reach its elastic limits.